Analysis of Fuel Cell Powered EV Charging Station - Bondu, Pavan Kumar Reddy (2024)
The paper offers a comparative performance analysis of fuel cell-powered EV charging systems utilizing ZETA, SEPIC, and modified SEPIC DC-DC converter topologies. Despite the cleaner energy source that fuel cells represent, their high cost has limited their penetration in EV charging. Selecting a suitable DC-DC converter topology is crucial for achieving fast charging and improved efficiency. The paper presents a performance analysis of the ZETA, SEPIC, and modified SEPIC converter topologies, both with open-loop and closed-loop control, for EV charging applications. A MATLAB/Simulink model was developed to examine the performance of these topologies in terms of battery state of charge (SoC), battery voltage, and charging current. The study reveals that the battery charged from an SoC of 50% to 50.03% using the modified SEPIC converter, while the ZETA and SEPIC converters charged to 50.024% under closed-loop control. Under open-loop control, the modified SEPIC charged to 50.025%, followed by ZETA at 50.024% and SEPIC at 50.02%, with a similar simulation time of ten seconds using a fuel cell as the primary energy source. The results demonstrate that the DC-DC modified SEPIC converter outperforms both ZETA and SEPIC converters.